Monitoring in real time the production of Fe-oxide nanoparticles. (22nd December 2015) - Fernández-García, M.P.; Teixeira, J.M.; Machado, P.; Enis Leblebici, M.; Lopes, J.C.B.; Freire, C.; Araujo, J.P.
Abstract: We herein demonstrate an in-situ device and a real time method to observe the vital stages of Fe-oxide nanoparticles' (NPs) preparation by coprecipitation reaction. The reaction volume is monitored by a home-made AC susceptometer to analyze the magnetic response of the growing NPs. Three different regions (nucleation, growth and diffusion) could be identified in the recorded in-phase and out-of phase curves. The morphological and magnetic characterization of the obtained Fe-oxide NPs reveal minute particle dimensions (<3 nm), narrow polidispersity (1–7 nm), superparamagnetic behavior (null coercivity) and narrow distribution of blocking temperatures (< TB > 67 K). We show that the device and technique enable real time assessment of the mixing speed which has paramount impact on the physical and chemical properties of the final product. Graphical abstract: Highlights: Assessment to the vital stages of Fe-oxide NPs' formation by coprecipitation. AC susceptometer to monitor in real time the magnetic response of the mixing volume. Nucleation, growth and diffusion identified on the in- and out-phase signals. Mixing reactants with pitch blade impellers allow narrow particle size distribution .